2021
DOI: 10.4236/health.2021.132010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occupational Stress and Related Risk Factors among Nurses Working in ASEER Region

Abstract: Background: Over the last century, stress as an interdisciplinary concept has become an area of great interest and has been researched extensively. Although the earliest studies on stress were mostly physiological, psychological models of stress have been developed and established a link between stressors and illness in his model of general adaptation syndrome. Objective: To investigate prevalence and factors associated with occupational stress among nurses working Asser region Hospital. The study included nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Although there is a wide range among different nursing groups and countries, recent prepandemic stress levels of health workers are similar (Aserri et al, 2021; Faremi et al, 2019; Sharma et al, 2014). This can be explained by the great social recognition of the profession and the realization of the enormous importance of the nursing profession, especially and more than ever in these extreme conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a wide range among different nursing groups and countries, recent prepandemic stress levels of health workers are similar (Aserri et al, 2021; Faremi et al, 2019; Sharma et al, 2014). This can be explained by the great social recognition of the profession and the realization of the enormous importance of the nursing profession, especially and more than ever in these extreme conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10 A further study conducted in a western region of Iran to measure the level of stress in PHC staff, and its predictive indicators found a prevalence of 52.9%. 11,12 Another study on nurses found that the majority of them (79%) were in the intermediate stress level, but roughly 14% were in the high stress level.…”
Section: Discussionmentioning
confidence: 99%
“…Aserri, Baddar, and Aserri [31] looked into the factors that contribute to occupational stress and how common it is among nurses who work at the Asser region hospital. Nurses from a range of age groups who worked in various departments participated in the study and had their sources of stress evaluated.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…There are seven items on the 4-point Likert scale: 0 connotes 'it didn't apply to me at all,' 1 connotes 'it applied to me somewhat or occasionally,' 2 connotes 'it applied to me a significant amount or frequently,' and 3 connotes 'it applied to me a great deal or most of the time'. After the addition of scores of each subscale levels and multiplying them by two, stress levels are therefore, categorized as follows: normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33) This study was conducted over the course of one (1) month and the activities involved enrolling participants for the study, which includes doctors and nurses, and collection of data.…”
Section: Data Collection Duration and Instrumentationmentioning
confidence: 99%